2017
DOI: 10.1186/s12888-017-1367-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of hair cortisol and dehydroepiandrosterone in mother-infant-dyads with maternal childhood maltreatment

Abstract: BackgroundChild maltreatment (CM) has severe effects on psychological and physical health. The hypothalamic-pituitary-adrenal (HPA) axis, the major stress system of the body, is dysregulated after CM. The analysis of cortisol and dehydroepiandrosterone (DHEA) in scalp hair presents a new and promising methodological approach to assess chronic HPA axis activity. This study investigated the effects of CM on HPA axis activity in the last trimester of pregnancy by measuring the two important signaling molecules, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 72 publications
1
23
1
Order By: Relevance
“…In agreement with other studies that have recently reported levels of steroid hormones in pregnant women using similar mass spectrometry methodologies [ 48 ] or radio-immunoassays [ 23 , 49 ], concentrations of most hormones reported in this study are lower than previously reported methods that employ either direct or indirect immunoassays. Hair cortisol is often cited as a surrogate for predicting maternal stress levels or a marker of hypothalamic–pituitary–adrenal axis function in pregnant women [ 50 , 51 , 52 , 53 ]; however, hair cortisol levels reported in many of these studies were measured using salivary cortisol immunoassays. In our study, hair cortisol and cortisone levels were below the levels of detection; in fact, progesterone was the only steroid hormone that was above the limit of detection in hair samples.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other studies that have recently reported levels of steroid hormones in pregnant women using similar mass spectrometry methodologies [ 48 ] or radio-immunoassays [ 23 , 49 ], concentrations of most hormones reported in this study are lower than previously reported methods that employ either direct or indirect immunoassays. Hair cortisol is often cited as a surrogate for predicting maternal stress levels or a marker of hypothalamic–pituitary–adrenal axis function in pregnant women [ 50 , 51 , 52 , 53 ]; however, hair cortisol levels reported in many of these studies were measured using salivary cortisol immunoassays. In our study, hair cortisol and cortisone levels were below the levels of detection; in fact, progesterone was the only steroid hormone that was above the limit of detection in hair samples.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that the earlier the traumatic stress takes place, the bigger the alterations [3], which, again, meshes well with the positive associations we found of cortisol and the cortisol/DHEA ratio with the timing of traumatic stress. A recent notable study tracks DHEA secretion following childhood adversity into the next generation, finding DHEA elevations in the hair samples of new mothers, as well as, on a more tentative level, in those of their newborn children [59], proving the substantial impact early life stress might have on DHEA secretion. However, other studies find no particular effects of adverse childhood events in juvenile and adult populations [28,33,34], highlighting the possible relevance of a plethora of further characteristics next to the timing of traumatic stress, such as type, duration and severity of the traumatic event, which urgently need assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, relatively little is known about the determinants of neonatal hair cortisol concentrations. Reports of whether neonatal hair cortisol reflects maternal cortisol in pregnancy are conflicting, with previous studies reporting either positive ( Hollanders et al, 2017 ) or no associations ( Hoffman et al, 2017b , Schury et al, 2017 ). Studies assessing determinants of neonatal hair cortisol in both humans and primate models have typically focused on maternal factors experienced throughout pregnancy, such as psychosocial stress ( Kapoor et al, 2016 , Romero-Gonzalez et al, 2018 , van der Voorn et al, 2018 ), and with the exception of one study ( Hollanders et al, 2017 ), have not reported associations between hair cortisol and exposures at the time of delivery.…”
Section: Introductionmentioning
confidence: 93%